Chemicals, noise and occupational hearing health in South Africa: A mapping study - Pillay M (AOSIS, 2020)
Background: Chemical exposure leading to ototoxicity is a fresh challenge for occupational healthcare in South Africa. Objectives: The critical question is: ‘what is known about occupational ototoxic chemicals with or without noise exposure in South Africa?’ Method: This qualitative, mapping study was completed with published (peer-reviewed) and grey literature from 1979-2019. Data was analysed using the Preferred Reporting Items for Systematic reviews and Meta-Analyses: extension for Scoping Reviews and the Nursing and Allied Health Resources Section subcommittee on Mapping the Literature of Nursing and Allied Health (adapted). Numerical analysis of article type was completed, but the primary focus was on capturing patterns/trends using thematic analysis and ideology critique. Results: The African Journal of Disability, African Journal of Primary Health Care and Family Medicine, South African Medical Journal, The South African Journal of Communication Disorders [SAJCD] and Health SA Gesondheid) were included with the SAJCD containing one relevant item and seventeen other items were analysed. Research focusses on the mining sector (gold) in Gauteng, and ototoxic medication (tuberculosis and/or human immunodeficiency virus) take precedence. In KwaZulu-Natal, the focus is on commerce and industry across formal and informal sectors. There are no governmental policies that refer to chemical ototoxicity. Occupational hearing loss is configured exclusively on the meme that noise exposure is the only toxin. Conclusion: Chemical exposures are only just beginning to be recognised as ototoxic in South Africa. Hearing conservation programmes should always serve the workers’ interests and never bow down to the econometric interests of employers.
© 2020. The Authors. Licensee: AOSIS.
Keywords: Audiology; Chemical; Hearing loss; Low- and middle-income countries; Mapping study; Occupational health; Ototoxicity; South Africa; Health Knowledge, Attitudes, Practice; Hearing Loss, Noise-Induced; Humans; Mining; Noise, Occupational; Occupational Diseases; Occupational Exposure; Qualitative Research; South Africa